Mental fortitude training: An evidence-based approach to developing psychological resilience for sustained success. Issue 3 (1st September 2016) - Fletcher, David; Sarkar, Mustafa
ABSTRACT: Drawing on the body of knowledge in this area, this article presents an evidence-based approach to developing psychological resilience for sustained success. To this end, the narrative is divided into three main sections. The first section describes the construct of psychological resilience and explains what it is. The second section outlines and discusses a mental fortitude training program for aspiring performers. The third section provides recommendations for practitioners implementing this program. It is hoped that this article will facilitate a holistic and systematic approach to developing resilience for sustained success.